Prevalence of sun‐protective behaviour and intentional sun tanning in German adolescents and adults: results of a nationwide telephone survey - Görig, Tatiana; Diehl, Katharina; Breitbart, Eckhard W.; Schneider, Sven (Journal of the European Academy of Dermatology and Venereology, 2018)
Abstract Background The incidence rate of melanoma in the Caucasian population is rising worldwide. One of the major environmental risk factors for melanoma is the exposure to ultraviolet (UV) radiation. To prevent skin damage caused by UV exposure, several organizations recommend wearing protective clothing, staying in the shade, avoiding the outdoors during midday and using sunscreen. Objective To provide representative data on factors associated with sun?protective behaviours and intentional sun exposure during summertime in the German population. Methods A population?based sample of 3000 German residents aged 14?45 years (response: 32.1%) was interviewed via telephone from October to December 2015. Survey participants provided data on the use of recommended sun?protective measures on a sunny summer day and their intentional sun exposure during summertime. Data were weighted by age, sex, educational level and federal state to ensure the national representativeness of the sample. Results Wearing long?sleeved clothes was the most frequently reported protective measure (53.9%), while wearing headgear was the least common (17.9%). Significantly lower frequencies of almost all recommended sun?protective measures were identified for males, participants between 14 and 25 years, those with an immigrant background and those with low levels of education. Using sun protection was positively associated with female gender (OR = 1.62), higher levels of education (ORhigh = 1.27), sunburn during childhood (OR = 1.33) and paying attention to healthy nutrition (OR = 1.64; all P < 0.05). Sun tanning behaviour was associated with female gender (OR = 1.42), younger age, lower level of education, sunbed use (OR = 5.24) and smoking status (OR = 1.50; all P < 0.001). Conclusion As individual sun?protective measures are easy to implement and provide effective protection against high?risk UV exposure, campaigns on skin cancer prevention in Germany should put a stronger focus on young adults, men, less educated individuals and those with immigration background.
First published: 02 June 2017
Gesehen am 08.05.2019